Leggere o interpretare Ausiàs March. - Grilli, Giuseppe (Scripta, 2022)
We read March in parallel with Carner, driven by the twentieth-century obsession with pure or intellectual poetry. Guided, both of them? Yes, because March in distinguishing between poetry of theatricality and egotistical poetry by miracle achieves a modernity that will take centuries to become intelligible. And in this sense he breaks all plausibility of chronology, as Yehoshua has done in recent years in a double piece of writing, a novel and an opera libretto.